2013
DOI: 10.1016/j.jcf.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

CFTR: Effect of ICL2 and ICL4 amino acids in close spatial proximity on the current properties of the channel

Abstract: These results highlight the critical role of these ICL residues in the assembly of the different domains and/or in the Cl(-) permeation pathway of CFTR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
0
17
0
3
Order By: Relevance
“…This difference may be attributable to the fact that a whole cell current measurement is a less direct readout of CFTR channel activity. Interestingly, Billet et al (27) did report that a double mutant in which the charges were swapped between these sites (E267R/K1060E) behaved like wild type CFTR in their assay, which is consistent with an electrostatic interaction between these residues that impacts CFTR activity. In sum, the present findings and these previous reports are in general agreement that E267 and K1060 play an important role in controlling CFTR channel activity that likely involves at least in part an electrostatic interaction between these residues.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…This difference may be attributable to the fact that a whole cell current measurement is a less direct readout of CFTR channel activity. Interestingly, Billet et al (27) did report that a double mutant in which the charges were swapped between these sites (E267R/K1060E) behaved like wild type CFTR in their assay, which is consistent with an electrostatic interaction between these residues that impacts CFTR activity. In sum, the present findings and these previous reports are in general agreement that E267 and K1060 play an important role in controlling CFTR channel activity that likely involves at least in part an electrostatic interaction between these residues.…”
Section: Discussionmentioning
confidence: 81%
“…This moderate degree of inhibition by the uncharged K1060T substitution is consistent with our findings. In a brief report Billet et al (27) observed that E267 and K1060 mutations reduced macroscopic (whole cell) CFTR currents in HEK-293 cells without obviously affecting protein maturation. These authors observed greater inhibition by a charge-reversal mutation than by a neutral substitution at the E267 position (E267R versus E267A), as we showed here in our more detailed mechanistic study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1B). Early homology modeling suggested that the TM extensions that make up the ICLs may form a narrow central "funnel" that forms a pathway for Cl Ϫ movement between the cytoplasm and the transmembrane pore formed by the TMs (9,10). However, such a funnel model was not supported by experiments investigating the functional effects of mutations within the ICLs on Cl Ϫ permeation (11,12).…”
mentioning
confidence: 99%